Isolation and characterization of vanadate-resistant mutants of Saccharomyces cerevisiae. - Willsky, G R (1985)
Cellular vanadium metabolism was studied in Saccharomyces cerevisiae by isolating and characterizing vanadate [VO4(3-), V(V)]-resistant mutants. Vanadate growth inhibition was reversed by the removal of the vanadate from the medium, and vanadate resistance was found to be a recessive trait. Vanadate-resistant mutants isolated from glucose-grown cells were divided into five complementation classes containing more than one mutant. Among the vanadate-resistant mutants isolated in maltose medium, the majority of mutants were found in only two complementation groups. Three of the classes of vanadate-resistant mutants were resistant to 2.5 mM vanadate but sensitive to 5.0 mM vanadate in liquid media. Two classes of vanadate-resistant mutants were resistant to growth in media containing up to 5.0 mM vanadate. Electron spin resonance studies showed that representative strains of the vanadate-resistant complementation classes contained more cell-associated vanadyl [VO2+, V(IV)] than the parental strains. 51 Vanadium nuclear magnetic resonance studies showed that one of the vanadate resonances previously associated with cell toxicity (G. R. Willsky, D. A. White, and B. C. McCabe, J. Biol. Chem. 259:13273-132812, 1984) did not accumulate in the resistant strains compared with the sensitive strain. The amount of vanadate remaining in the media after growth was larger for the sensitive strain than for the vanadate-resistant strains. All of the strains were able to accumulate phosphate, vanadate, and vanadyl.